A strategic approach to brand definitions - Ρηγοπούλου, Ειρήνη Δ. (SPOUDAI Journal of Economics and Business, 2002)
In the context of developing a theory relevant to the term "Brand", this article focuses on how "Brands" are perceived by executives active in Greece. Based on the empirical research undertaken, useful conclusions have been reached regarding the "Brand", as it is perceived by business executives. Apart from that, this article expresses a view of how the practitioners should perceive the Brand, so that, under the scope of Strategic Brand Management, to achieve the development of strong Brands.